2007
DOI: 10.1158/0008-5472.can-07-0702
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Protein Translation in Human Non–Small Cell Lung Cancer via Combined MEK and Mammalian Target of Rapamycin Suppression

Abstract: Lung cancer is a genetically heterogeneous disease characterized by the acquisition of somatic mutations in numerous protein kinases, including components of the rat sarcoma viral oncogene homolog (RAS) and AKT signaling cascades. These pathways intersect at various points, rendering this network highly redundant and suggesting that combined mitogen-activated protein/extracellular signal-regulated kinase (MEK) and mammalian target of rapamycin (mTOR) inhibition may be a promising drug combination that can over… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 44 publications
5
56
1
Order By: Relevance
“…This is one of the main reasons for the relative failure of the first generation single-targeted inhibitors such as gefitinib and erlotinib. Therefore, preclinical studies highlighted that combined treatment with targeted inhibitors that concurrently block multiple signaling pathways produced synergistic antitumor activity (31,32). Our data showed that synergistic growth inhibitory effects of GDC-0941 in combination with U0126 were observed in A549 and H460 cells, further verifying the importance of multi-targeted therapeutics.…”
supporting
confidence: 56%
“…This is one of the main reasons for the relative failure of the first generation single-targeted inhibitors such as gefitinib and erlotinib. Therefore, preclinical studies highlighted that combined treatment with targeted inhibitors that concurrently block multiple signaling pathways produced synergistic antitumor activity (31,32). Our data showed that synergistic growth inhibitory effects of GDC-0941 in combination with U0126 were observed in A549 and H460 cells, further verifying the importance of multi-targeted therapeutics.…”
supporting
confidence: 56%
“…Notably, clinical successes with rapamycin analogs as single agents have been limited (Sawyers 2003;Guertin and Sabatini 2007), with some notable exceptions (Cloughesy et al 2008;Le Tourneau et al 2008). In contrast, rapamycin analogs have been shown to be more promising in combination with standard chemotherapy or agents that target other signaling pathways, particularly the RAS/MEK/MAP kinase pathway (Wang et al 2006;Wendel et al 2006;Fan et al 2007;Legrier et al 2007;Carracedo et al 2008;Kinkade et al 2008). Therefore, while rapamycin analogs represent a promising strategy in the treatment of invasive bladder cancer, it will also be important to investigate their efficacy in combination with other targeted therapies and/or chemotherapy (Shah and McKiernan 2004;Sonpavde et al 2008;Wallerand et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, we have previously demonstrated that multitargeted suppression of the RAS-PI3K signaling network by MEK inhibition in combination with rapamycin is synergistic in numerous cancer cell models. This mechanism is via potent suppression of cap-dependent translation and dephosphorylation of S6 and 4E-BP1 (27). Transcriptome profiling indicates that p53 signaling is involved in disco-induced senescence.…”
Section: Discussionmentioning
confidence: 99%